GAYA KEPEMIMPINAN, IKLIM ORGANISASI, MOTIVASI KERJA DAN KINERJA APARATUR - ', Aliadam (Jurnal Ilmu Administrasi Negara, 2016)
Leadership Style, Organizational Climate and Work Motivation Performance Against Apparatus. This study aimed to analyze the influence of leadership style, organizational climate and work motivation on the performance of personnel offices of cooperatives and SMEs in Riau. This research method is survey method with quantitative approach. The study population is all employees amounted to 93 people and a sample of the entire population (census). Data obtained by distributing questionnaires to the respondents as many as 93 respondents. Analysis of the data used is linear regression analysis. These results indicate that partially leadership style affect the performance of the apparatus, organizational climate affect the performance aparatu, motivation affect the performance of the apparatus. Simultaneously style of leadership, organizational climate and work motivation affect the performance of the apparatus with koofesien value of determination (R2) of 0.924. That is 92.4% office apparatus performance Cooperatives and SMEs Riau province influenced by the style of leadership, organizational climate and work motivation and 7.6% influenced by other factors.